Evolución paleoceanográfica del Oceáno Austral (sectores subantárticos del Atlántico y Pacífico) durante el Plioceno tardio-Pleistoceno - Ballegeer, Anne-Marie Clara (2011)
[ES] Esta tesis examina el registro de nanofósiles calcáreos de los testigos 1090 (Atlántico Sur) y 1172 (Pacífico Sur) del Ocean Drilling Program (ODP) durante el Plio-Pleistoceno (3.5-1.8 Ma). Los nanofósiles calcáreos (cocolitofóridos) son una excelente herramienta para monitorizar las condiciones de las aguas superficiales del Océano Sur dado que son sensibles a diferentes factores ambientales como la luz, temperatura y concentración de nutrientes. Los registros de nanofósiles han sido comparados con los isótopos bentónicos para reconstruir los cambios paleoceanográfi cos del Océano Sur durante el intervalo de estudio. [EN] This thesis examines the record of calcareous nannofossils witnesses 1090 (South Atlantic) and 1172 (South Pacific) from Ocean Drilling Program (ODP) during the Plio-Pleistocene (3.5-1.8 Ma). The calcareous nannofossils (coccolithophores) are an excellent tool to monitor the conditions of the Southern Ocean surface waters because they are sensitive to different environmental factors such as light, temperature and nutrient concentration. Nannofossils records have been compared with the benthic isotope paleoceanography to reconstruct changes cos Southern Ocean during the study interval.